Your Patient Has Congenital Heart Disease—What Questions Should You Ask to Provide High-Quality Care?. Issue 4 (July 2015) - McRae, Marion E.
Abstract : Congenital heart disease (CHD) is the most common birth defect. About two-thirds of those individuals living with CHD are now adults. If you do not have in-depth knowledge of CHD, knowing what questions to ask and what resources to use can improve patient outcomes and satisfaction with care.